Unraveling the Mysteries of Acute Flaccid Myelitis: Scientific Opportunities and Priorities for Future Research. (22nd September 2020) - Lerner, Andrea M; DeRocco, Amanda J; Yang, Linda; Robinson, Daphne A; Eisinger, Robert W; Bushar, Nicholas D; Nath, Avindra; Erbelding, Emily
Abstract: Since 2014, cases of acute flaccid myelitis (AFM) have been reported in the United States in increasing numbers biennially, occurring in the late summer and early fall. Although there is unlikely to be a single causative agent of this syndrome, non–polio enteroviruses, including enterovirus D-68 (EV-D68), have had epidemiological and laboratory associations with AFM. Much remains to be known about AFM and AFM-associated enteroviruses, including disease pathogenesis and the best strategies for development of therapeutics or preventive modalities including vaccines. To catalyze research that addresses these scientific and clinical gaps, the National Institute of Allergy and Infectious Diseases convened a workshop entitled "AFM Preparedness: Addressing EV-D68 and Other AFM-Associated Enteroviruses" on 19–20 February 2020. Abstract : Cases of acute flaccid myelitis (AFM) have been increasingly reported since 2014. Epidemiological and laboratory associations make EV-D68 and other AFM-associated enteroviruses logical initial targets for medical countermeasures. A workshop was convened to address knowledge gaps and identify research priorities.